(untitled) (Tanzania Journal for Population studies and Development, 2013)
The Marine and Coastal Environmental Management Project (MACEMP) was conceived as a response to local, national and global concerns on sustainable conservation and use of marine and coastal resources. It has been involved in facilitating fisheries management for the purpose of empowering coastal communities to access opportunities so that they can request, implement and monitor sub-projects that contribute to improve livelihoods and sustainable marine ecosystem management, e.g., aquaculture. This paper assesses MACEMP by looking at the welfare implication between the treatment group and the control group using household and village level survey data collected from Mafia District in Coast region. Data were collected using questionnaire, interviews and field observation. In analyzing the information collected the study utilized Principal Component Analysis (PCA) method, descriptive statistics, and regression analysis. Results of all methods of analysis show that the project has positive impact on poverty reduction in Mafia District as revealed by the differences in poverty status between the treatment group and the control group.